Nurses’ roles in caring for the brain-dead organ donors in a clinical ward - Chuawong, Panatchaya; Khunkaew, Saneh; Sawangket, Amonrat (Thai Journal of Nursing, 2020)
Nowadays, the technology in organ transplantation has been rapidly developed. Preparing the brain- dead organ donors is important in order to maintain the organ function. Nurses have significant roles in taking good care of these donors among the multidisciplinary health team. This article will present the nurses’ roles in preparing the brain- dead organ donors including the roles of organ keeper to maintain the organ function, an infection controller to promote safety for organ donors , and a holistic care giver to enhance humanized care and dignity of the organ donors and their families.